ADVANCING ESSAY WRITING WITH DIGLIT: APPLICATION AND EFFECTIVENESS OF A DIGITAL LITERACY TEACHING TOOL - Hidayati, Istiqlailah Nurul; Dewanti, Ratna; Rasyid, Yumna; Putra, Purnama (University of Kuningan, 2024)
Writing an essay is still a challenge for students even for those at the university level. There are many difficulties they find when they try to write it. First, especially in non-English speaking countries, students lack vocabulary, they do not have ideas to write, they are still confused about the mechanics, and they find it difficult to organize the writing. Since the problems are complex, giving only the theories of writing to the students is not adequate. Teachers have to ‘arm’ the students with tools. There are many tools available today on the internet, yet not many students are able to use them correctly. They need guidance to use them in the correct way. This research aims at developing a digital teaching tool to assist students in writing an essay. The research is done by doing need analysis, designing the digital tool, and finally testing the designed teaching tool. The digital teaching tool is named as Diglit which stands for Digital Literacy. It is named so since the tool guides the students to use their literacy skills for constructing a better essay. The research employed ASSURE design to develop the teaching tool. At the end of the process, the tool is tested for its effectiveness using quasi experimental research and it is found out that there is an effect of the use of Diglit on the students’ writing skill. Hence, the result shows that the digital tool created from the research is able to help the students construct an essay.